(untitled) (Eureka Journal of Artificial Intelligence and Data Innovation, 2026)
This article examines the role of Unmanned Aerial Vehicles (UAVs) in 21st-century border conflicts and hybrid warfare, highlighting their tactical and strategic advantages as well as the emerging threats they pose to national security. Drawing on the insights and experiences from recent conflicts, such as the Russia-Ukraine war and the Nagorno-Karabakh conflict, the study analyzes how the evolution of drone technology is fundamentally reshaping border defense and protection frameworks.